2019
DOI: 10.1108/jmp-10-2018-0443
|View full text |Cite
|
Sign up to set email alerts
|

Career implications for high-quality work relationships: an SCCT test

Abstract: Purpose Researchers recognize that interpersonal relationships contribute to the career development of professional employees. The purpose of this paper is to extend this research to individuals working at a formative point in their careers. Guided by Social Cognitive Career Theory, a model is developed that tests whether the quality of individuals’ work relationships at an early career stage has implications for their development of career cognitions and career exploration behaviors. Design/methodology/appr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 43 publications
(58 reference statements)
0
14
0
Order By: Relevance
“…A sample item was, "I expect that my career will be fulfilling," and response options were 1 ¼ strongly disagree to 7 ¼ strongly agree. Recent research has shown this measure to be reliable (e.g., a ¼ .86 and .88 in two samples, Ehrhardt & Sharif, 2019) and valid given its relationship with other career-oriented constructs such as career self-efficacy (r ¼ .49 and .59 in two samples, Ehrhardt & Sharif, 2019).…”
Section: Methodsmentioning
confidence: 99%
“…A sample item was, "I expect that my career will be fulfilling," and response options were 1 ¼ strongly disagree to 7 ¼ strongly agree. Recent research has shown this measure to be reliable (e.g., a ¼ .86 and .88 in two samples, Ehrhardt & Sharif, 2019) and valid given its relationship with other career-oriented constructs such as career self-efficacy (r ¼ .49 and .59 in two samples, Ehrhardt & Sharif, 2019).…”
Section: Methodsmentioning
confidence: 99%
“…Indeed, past research suggests that employees feel more attached and committed to their careers when they experience a friendly working environment at work (Somers et al, 2018;Wickramasinghe, 2016). Ehrhardt and Sharif (2019) also found that the quality of relationships positively impacts employees' career-related behavior. Closeness and attachment with others at the work not only enhance employees' energy, vitality or positive emotions (Khazanchi et al, 2018), but also enhance their potential and improve their psychological state/well-being (Abugre, 2017;Madden et al, 2015).…”
Section: Social Support Received At Work and Relational Attachmentmentioning
confidence: 99%
“…For instance, Karatepe and Olugbade (2017) (Abugre, 2017;Colbert et al, 2016;Feeney and Collins, 2019). More specifically, in a recent study, Ehrhardt and Sharif (2019) found that employees receiving social support at work enhances their attachment and closeness with others at work (i.e. relational attachment).…”
Section: Mediating Role Of Relational Attachmentmentioning
confidence: 99%
“…Ghosh et al (2019) find that TMX is positively related to individual innovation work behavior, which refers to whether a person has implemented creative ideas into innovative behavior. Moreover, Ehrhardt and Sharif (2019) find that a coworker relationship increases an individual's career self-efficacy and leads one to explore new career opportunities. The above findings suggest that high-quality TMX is conducive to the generation of creative ideas.…”
Section: Tmx and Creativitymentioning
confidence: 99%